The last natural seasonal forests of Indonesia: implications for forest management and conservation - Laumonier, Y.; Nasi, R. (Wiley, 2018)
The status, type and ecology of the vegetation of the southeastern seasonal regions of Indonesia need to be clarified to identify adequate natural resource management and conservation strategies.Tanimbar archipelago represents a group of islands south of the Banda sea in the Moluccas. The largest is the flat Yamdena (7°36′ S, 131°25′ E).Vegetation was interpreted from LANDSAT satellite data, overlaid with geology and topography for pre‐stratification. Within each strata, forest sites were equally systematically sampled using a network of small 0.2 ha survey plots (60 plots, 7,130 trees) and soil pits sampled for 44 of the vegetation plots. Fisher’s alpha diversity index was used together with ordination techniques to assert differences in forest types.The forest covered c. 70% of the island, comprising seasonal evergreen forest (SEF), dry deciduous forest (DDF) and moist deciduous forest’ (MDF). The SEF canopy (Burseraceae, Meliaceae, Oleaceae and Dilleniaceae) sited around 35 m. The density of trees above 10 cm diameter averaged 632 individuals/ha, the basal area (BA) was 32 m2/ha, and species diversity (SD, Fischer α) 14.84. Rattans are abundant in the understorey. The MDF exhibited a mixture of evergreen and deciduous big trees while the lower storey was evergreen. Rattans were less common. Distinct family species associations emerged from the ordination (Combretaceae, Fabaceae, Malvaceae and Apocynaceae or Meliaceae, Gnetaceae, Clusiaceae). The density of trees averaged 491 individuals/ha, BA 26 m2/ha and SD 18.73. The canopy of the DDF (Ebenaceae, Fabaceae, Apocynaceae and Menispermaceae) was around 30 m. During the dry season all tree species shed their leaves. The density of trees averaged 552 individuals/ha, BA 20 m2/ha and SD 11.58.The last natural seasonal forests of Indonesia are nowadays only found in the Tanimbar Archipelago. The existence of three contrasted seasonal forest types on small flat island was remarkable and should be quickly translated into decision making for land zoning, agriculture or forestry development, avoiding approaches applied in the humid region of the country. To succeed however, the ecology of these seasonal forests should quickly become priority areas for research to feed the design of suitable conservation and management strategies.